Managing Human Resources : Human Resource Management in Transition. - Bach, Stephen; Edwards, Martin (Hoboken : Wiley, 2012)
This revised edition is a comprehensive, authoritative set of essays. It is more detailed and analytical than the mainstream treatments of HRM. As in previous editions, Managing Human Resources analyses HRM, the study of work and employment, using an integrated multi-disciplinary approach. The starting point is a recognition that HRM practice and firm performance are influenced by a variety of institutional arrangements that extend beyond the firm. The consequences of HRM need to incorporate analysis of employees and other stakeholders as well as the implications for organizational performance.
Wider Implications and Conclusions.
Print version record.
Keywords: Personnel management -- Great Britain; Personnel management -- Great Britain; Personnel management; Electronic books